Observational study of the safety of buprenorphine+naloxone in pregnancy in a rural and remote population. Issue 10 (31st October 2016) - Jumah, Naana Afua; Edwards, Craig; Balfour-Boehm, Jazmyn; Loewen, Kassandra; Dooley, Joseph; Gerber Finn, Lianne; Kelly, Len
Abstract : Objectives: To describe the effect of in utero exposure to the buprenorphine+naloxone combination product in a rural and remote population. Setting: A district hospital that services rural and remote, fly-in communities in Northwestern Ontario, Canada. Participants: A retrospective cohort study was conducted of 855 mother infant dyads between 1 July 2013 and 30 June 2015. Cases included all women who had exposure to buprenorphine+naloxone during pregnancy (n=62). 2 control groups were identified; the first included women with no opioid exposure in pregnancy (n=618) and the second included women with opioid exposure other than buprenorphine+naloxone (n=159). Women were excluded if they had multiple pregnancy or if they were part of a methadone programme (n=16). The majority of women came from Indigenous communities. Outcomes: The primary outcomes were birth weight, preterm delivery, congenital anomalies and stillbirth. Secondary neonatal outcomes included gestational age at delivery, Apgar scores at 1 and 5 min, NAS Score >7 and treatment for neonatal abstinence syndrome (NAS). Secondary maternal outcomes included the number of caesarean sections, postpartum haemorrhages, out of hospital deliveries and transfer of care to tertiary centres. Results: No difference was found in the primary outcomes or in the Apgar score and caesarean section rate between in utero buprenorphine+naloxone exposure versus no opioid exposure in pregnancy. Compared to women taking other opioids, women taking buprenorphine+naloxone had higher birthweight babies (p=0.001) and less exposure to marijuana (p<0.001) during pregnancy. Conclusions: Retrospective data suggest that there likely is no harm from taking buprenorphine+naloxone opioid agonist treatment in pregnancy. Larger, prospective studies are needed to further assess safety.